Sistem Perlindungan Atas Ciptaan Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta Dalam Perspektif Cyber Law - Sudjana, Sudjana (Faculty of Law, Parahyangan Catholic University, 2016)
AbstractThe purpose of this article is to discuss, from the perspective of cyber law, the relevant rules and regulation as found in the prevailing law on copyright (Law No. 28 of 2014) and how it provides effective protection to copyright creations. The author shall highlight the most important rules and norms or principles. The discussion shows that a number of rules in the Law No. 28 of 2014 has not been able to fully accommodate the need to respond to new development in virtual technology. A number of issues concerning who enjoy protection, the object being protected, registration system, period of protection, restriction on copyright and its relation to educational interest and scientific research still needs to be regulated in detail.